Serotype distribution and antimicrobial resistance of streptococcus pneumoniae in children with acute bacterial meningitis in Mozambique: implications for a national immunization strategy - Nhantumbo, Aquino Albino (2016)
Produção científica do Laboratório de Hanseníase.